2021
DOI: 10.3389/fcimb.2020.566661
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Dendritic Cells and Candida krusei β-Glucan Partially Depends on Dectin-1 and It Promotes High IL-10 Production by T Cells

Abstract: Host-Candida interaction has been broadly studied during Candida albicans infection, with a progressive shift in focus toward non-albicans Candida species. C. krusei is an emerging multidrug resistant pathogen causing rising morbidity and mortality worldwide. Therefore, understanding the interplay between the host immune system and C. krusei is critically important. Candia cell wall β-glucans play significant roles in the induction of host protective immune responses. However, it remains unclear how C. krusei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…Dectin-1 can trigger DCs to drive T cell responses against several different fungal pathogens, bacteria, viruses and tumors [19,20]. In this study, our data showed that β-glucans promote the expression of Dectin-1 in BMDCs, which may activate downstream signals to produce an immune response [21]. Mature DCs can express remarkable levels of the costimulatory molecules CD80/86, which promote T cell activation for immune function.…”
Section: Discussionmentioning
confidence: 58%
“…Dectin-1 can trigger DCs to drive T cell responses against several different fungal pathogens, bacteria, viruses and tumors [19,20]. In this study, our data showed that β-glucans promote the expression of Dectin-1 in BMDCs, which may activate downstream signals to produce an immune response [21]. Mature DCs can express remarkable levels of the costimulatory molecules CD80/86, which promote T cell activation for immune function.…”
Section: Discussionmentioning
confidence: 58%
“…The expression of CLEC7A was decreased upon treatment with WGP-Dispersible and Zymosan, but not with WGP-Soluble (Supplementary Figure 7). Previous reports have shown a downregulation of Dectin-1 expression on the surface of human monocyte-and mouse bone marrow-derived dendritic cells and mouse bone marrow-derived macrophages in response to particulate b-glucan stimulation (39)(40)(41). However, no mention was made therein whether CLEC7A gene expression was also reduced.…”
Section: Bovine Monocyte Stimulationmentioning
confidence: 96%
“…Previous reports showed that b-glucan adjuvanticity increases the expression of co-stimulatory molecules like CD86 and CD40 in dendritic cells via direct activation of Dectin-1, however, no training induced effects have been reported. 24,25 Therefore, we first tested if b-glucan training improved the expression of co-stimulatory molecules such as CD86 and CD40 on BMDMs in an in-vitro training model. In this experiment, 3 million BMDMs were trained with either PBS (untrained) or 100 µg/mL of b-glucan for 24 h in a 12-well plate with a total volume of 2 mL.…”
Section: In-vitro B-glucan Training In Antigen Presentationmentioning
confidence: 99%